Análisis de los canticos futbolísticos y su influencia en la identidad de la hinchada ecuatoriana - Insuasti Saltos, Marco Antonio (2013)
This documentis intendedas a basisfor future researchinEcuador, as they arelittleor noresearchregarding thisissue, we are lookingto contribute to theknowledge ofthis social phenomenon, the effect thathavein our society andtheimportance of thisissuein our environment. Shall be basedon the basis ofa descriptive and bibliographical investigationdeveloped with topics that arerelated with theCommunication, Journalism, Speech, Discourse Analysis, Semiotics, Sport, Soccer, “BarrasBravas”, Soccerchants, RhetoricalFigures, etc.., Sameas detailedin fourstudychapters, to increase a little the knowledge “BarrasBravas” is related a group offansorganized as awell-definedstructureof people who supporta soccer team. The main objectiveof this thesisis to analyzethe contents ofsoccerchantsto determinethe concept and meaningof the messages thatare transmitted tothe fans of the more representative soccer teams in Ecuador as: Club Sport Emelec, Barcelona Sporting Club, LigaDeportivaUniversitaria de Quito y SociedadDeportivo Quito, Theyhave excellednot only forplaying technique,but also bytheir organizationin groups called “BarrasBravas” that usechantsof encouragementusingmanycases createdandothersinfluenced byforeign teamsthat are expressedinthe standsofsportingscenarios of thecountry. Through followingpages we will tryto shownot onlytheresearch,but alsoto describewhat that means tothe fanstheir team, because that´s considered astheir second family, trying to dowith thatawarenessin eachof us toeradicate the cultureof violence thatgripped theeveryday life ofsociety.